Thou Shalt Not! – How the institutional afterlife of research misconduct scandals shapes research integrity training - Serge P.J.M. Horbach; Rachel Fishberg; Sven Ulpts; Lise Degn (Journal of Responsible Innovation)
Scandals involving cases of research misconduct are often considered to be main drivers for policy initiatives and institutional changes to foster research integrity. These impacts of scandals are usually witnessed during scandals’ peak visibility. In this article we change this perspective by examining the way in which scandals continue impacting academic institutions long after the initial attention has faded. To do so, we empirically study research integrity courses at multiple Danish universities. We combine data from document analysis, participatory observations and interviews. In addition, this article makes a conceptual contribution by introducing the notion of the ‘institutional afterlife’ of a scandal. We use this notion to demonstrate how scandals can affect academic communities and practices long after their initial visibility has faded, by re-entering communities and institutions. We thereby contribute a novel approach to studying scandals and their wider implications in academia.